Density-dependent effects on the survival and growth of the rodent stomach worm Protospirura muricola in laboratory mice - Lowrie, Fiona M.; Behnke, Jerzy M.; Barnard, Christopher J. (Cambridge University Press, 2004)
The spirurid nematode, Protospirura muricola, is of intrinsic interest as a rodent model of gastric nematode infections. Since worm burdens can be very heavy in nature, density dependent processes may constrain parasite growth. Laboratory mice (BKW) were exposed to varying doses of infective larvae of P. muricola in the range 5 to 40 third-stage larvae (L3), in four separate experiments in which progressively higher doses were utilized. All mice were culled 60 days after infection and a total of 518 worms (226 male and 292 female worms) was recovered, measured and weighed. Overall survival was 58.9%, but survival declined significantly with increasing dose by approximately 21% (from 66% at 5 L3 per mouse to 52% at 40 L3 per mouse). The length and weight of worms correlated positively in both sexes. Total worm biomass increased linearly with increasing numbers of worms. However, whilst the length and weight of male worms declined with increasing worm burden (8.4 and 24.6% respectively), female worms were less affected, only length showing a significant reduction with increasing parasite burden (16.0%). Therefore, increasing worm burdens impeded growth of P. muricola, but reduction in length and weight were relatively small in relation to the overall size of this nematode. Increasing worm burdens were associated with loss of host weight and reduction in stomach weight and worm burdens in excess of 20 exerted a measurable cost to the host, which in the field, may be associated with loss of overall host fitness.